Building Blocks of Resilience: Applications for Justice Involved Youth (Journal of Applied Juvenile Justice Services, 2020)
This paper describes potential benefits and empirical support for applying key components of Resilience theory and its associated models to intervention strategies within the field of juvenile justice. Traditionally, practitioners have utilized aspects of resilience theory for clients and patients within psychology, social work, and medicine. However, emerging research has demonstrated that the process of positively coping with risk can minimize factors that promote delinquency and criminality. Results have demonstrated that constructs such as low self-esteem, school detachment, poor socialization, and environmental influences can be positively affected by implementing critical features of resiliency. Additionally, implications are provided for practitioners seeking to develop or improve intervention programs such as restorative justice, and recommended areas for further research are provided.